Gut microbial transformation of the dietary mutagen MeIQx may reduce exposure levels without altering intestinal transport. (September 2019) - Zhang, Jianbo; Empl, Michael T.; Schneider, Mirjam; Schröder, Bernd; Stadnicka-Michalak, Julita; Breves, Gerhard; Steinberg, Pablo; Sturla, Shana J.
Abstract: The mutagen and probable human carcinogen 2-amino-3, 8-dimethylimidazo[4, 5- f ]quinoxaline (MeIQx) is metabolized in the colon to 9-hydroxyl-2, 7-dimethyl-7, 9, 10, 11-tetrahydropyrimido[2′, 1′:2, 3]imidazo[4, 5- f ]quinoxaline (MeIQx-M1) by conjugation with microbially generated acrolein. However, whether this microbiota-controlled process alters systemic exposure and hepatotoxicity of MeIQx remains unclear. The physiological relevance of this microbial transformation on the systemic exposure of MeIQx was investigated using an in vitro-in vivo extrapolation approach. To address whether microbial transformation influences intestinal transport of MeIQx, the intestinal uptake of MeIQx and its metabolite MeIQx-M1 was quantified using Ussing chambers mounted with different intestinal segments from male Fischer 344 rats. Up to 0.4% of both MeIQx and MeIQx-M1 were transported from the mucosal side to the serosal side of intestinal tissue within 90 min, suggesting that the intestinal uptake of both compounds is similar. With the uptake rates of both compounds, physiologically based pharmacokinetic (PBPK) modeling of the fate of MeIQx in the human body including microbial transformation of MeIQx was performed. Results indicate for the first time that high levels of microbe-derived acrolein would be required to significantly reduce systemic exposure of MeIQx in humans. Finally, neither MeIQx nor MeIQx-M1 were cytotoxic towards human liver HepaRG cells at dietary or higher concentrations of MeIQx. In summary, these findings suggest that gut microbial transformation of heterocyclic amines has the potential to influence systemic human exposure to some extent, but may require significant gut microbial production of acrolein and that further investigations are needed to understand physiological levels of acrolein and competing biotransformation pathways. Highlights: Intestinal transport of MeIQx and MeIQx-M1 is quantified. Cytotoxicity of MeIQx and MeIQx-M1 towards human liver cells is determined. Physiologically based pharmacokinetic modeling including gut microbial transformation is established. Microbially derived acrolein reduces systemic exposure of MeIQx in humans by up to 4-fold.